Differential susceptibility to insecticides by Leptinotarsa decemlineata [Coleoptera: Chrysomelidae] populations from western Canada - Noronha, C.; Duke, G.M.; Chinn, J.M.; Goettel, M.S. (Phytoprotection, 2001)
The susceptibility of Colorado potato beetles (Leptinotarsa decemlineata) (CPB) from three provinces in western Canada was measured using a filter paper bioassay to substantiate the reported insecticide resistance by the beetle in Manitoba, and to compare the situation there to beetle populations from Saskatchewan and Alberta. Susceptibility of beetles was measured against five insecticides: the organophosphates, azinphos-methyl (Guthion), and methamidophos (Monitor); the pyrethroid, permethrin (Ambush); the organochlorine, endosulfan (Endosulfan); and the carbamate, carbaryl (Sevin). All 12 populations tested from Manitoba were found to have resistance to one or more of the insecticides. All populations were classified as either having resistance or intermediate resistance to permethrin; two of the populations were classified as having resistance to azinphos-methyl and three to methamidophos. Two of four populations from Saskatchewan were classified as having intermediate resistance to azinphos-methyl and methamidophos. Intermediate resistance to permethrin was recorded in 12 of the 13 populations from Alberta, with only one being highly susceptible. Two populations showed evidence of intermediate resistance to azinphos-methyl and three to methamidophos. In all three provinces, survival rate from different egg masses within the susceptible populations ranged from 0-100%, indicating the presence of individuals with either resistance, intermediate or high susceptibility within these populations. With the expanding potato acreage in western Canada and the detection of the CPB populations with resistance to insecticides, a resistance management program must be implemented to prevent the rapid selection of resistant populations.